The Development of the Right of Access as a Part of Human Rights - Roszewska, Katarzyna (PRAWO i WIĘŹ, 2023)
Research on accessibility has been intensified due to CRPD. Sometimes, even a new discipline of accessibility studies, separate from disability studies, is distinguished. It is a broad field at the intersection of all disciplines whose theory and practice concern various aspects and areas of accessibility. It needs to be defined as its discipline, with its unique set of methods, ideas, and models. There is undoubtedly a lack of in-depth consideration of accessibility in legal studies. Accessibility has not yet received such considerations as Disability Law or Disability Legal Studies. Accessibility Law awaits similar discussion on its place in the legal studies and legal system. Undeniably, the legal standards of accessibility included in the crPD are part of human rights law. What is missing, however, is an in-depth consideration of how far Disability Law should be seen as a subdiscipline of human rights law, in which the crPD has played a crucial role, and in how far it is already becoming a separate discipline. Inthe development of the accessibility law, issues related to identifying other sources and the place of accessibility in the legal system, its role, its legal nature and the scope of accessibility standards can be distinguished. Attemptsare made to assess the content of the Convention concerning accessibility, to analyze General Comment No. 2 (2014) „Article 9 Accessibility”,and to review the subject literature on accessibility law. Detailed legal solutions within the different areas of accessibility are slowly emerging. Lawyers maystruggle with the relationship between the normative and technical content of accessibility. Thus, it becomes important to provide not only legal guarantees but also guarantees of complementary technical standards. Finally, althoughaccessibility is considered in the context of an international human rights standard, its assessment is not insignificant from a regional or national perspective, including the role of soft law and governance in promoting the rights of persons with disabilities at the EU level.